Adult Prevalence of Epilepsy in Spain: EPIBERIA, a Population-Based Study - Pedro J. Serrano-Castro; Jose Angel Mauri-Llerda; Francisco José Hernández-Ramos; Juan Carlos Sánchez-Alvarez; Beatriz Parejo-Carbonell; Pablo Quiroga-Subirana; Fernando Vázquez-Gutierrez; Sonia Santos-Lasaosa; Carolina Mendez-Lucena; Luis Redondo-Verge; Carlos Tejero-Juste; Clara Morandeira-Rivas; et al. (The Scientific World Journal)
Background. This study assesses the lifetime and active prevalence of epilepsy in Spain in people older than 18 years. Methods. EPIBERIA is a population-based epidemiological study of epilepsy prevalence using data from three representative Spanish regions (health districts in Zaragoza, Almería, and Seville) between 2012 and 2013. The study consisted of two phases: screening and confirmation. Participants completed a previously validated questionnaire (EPIBERIA questionnaire) over the telephone. Results. A total of 1741 valid questionnaires were obtained, including 261 (14.99%) raising a suspicion of epilepsy. Of these suspected cases, 216 (82.75%) agreed to participate in phase 2. Of the phase 2 participants, 22 met the International League Against Epilepsy’s diagnostic criteria for epilepsy. The estimated lifetime prevalence, adjusted by age and sex per 1,000 people, was 14.87 (95% CI: 9.8–21.9). Active prevalence was 5.79 (95% CI: 2.8–10.6). No significant age, sex, or regional differences in prevalence were detected. Conclusions. EPIBERIA provides the most accurate estimate of epilepsy prevalence in the Mediterranean region based on its original methodology and its adherence to ILAE recommendations. We highlight that the lifetime prevalence and inactive epilepsy prevalence figures observed here were compared to other epidemiological studies.